Digitization of Arabic materials in IIUM Library : challenges and problems - Abdullah, Sarifah; Marsidi, Suhaila (2006)
The International Islamic University Malaysia (IIUM) Library’s mission is to be an excellent information centre providing information to meet the learning, teaching, and research needs of its customers. Its information resources are predominantly in English and Arabic, with a minor portion in Malay, Persian, Urdu, Chinese, and other languages. Arabic language materials comprise of 30% of the collection. To make the resources readily accessible “anytime” and “anywhere” the Library embarked in a digital library project in 2001 and its full implementation started in 2004. The need for Arabic language capabilities has always been one of the Library’s major requirements. The system fully supports Arabic, able to publish Arabic information online, and provides full-text access. The whole process of making the resources accessible online involves various activities such as digitizing, indexing, digital object management and web publishing. The current system has many strengths, however it also has areas for improvement. This paper shares the Library’s experience in implementing a digital library system, focusing on the challenges in digitizing Arabic language information resources